Prevalence and importance of choosing health and physical education subject in Tamil- Medium secondary schools in the Colombo Central Zone, Sri Lanka - Barath, N. (University of Jaffna, 2024)
In 1932, C.W.W. Kannangara, known as the father of free education, incorporated health as a subject in the Kanthassa education system within the Sri Lankan curriculum. The subject was further developed in 1980 and subject named as Health and Physical education. The aim of the study is to assess prevalence of the students who selected the Health and Physical education as a subject and the participants’ view about the importance of this subject among Tamil medium Schools of Colombo Central Zone. Mixed methods research design was used. There are 22 Tamil-medium secondary schools in the Colombo Central Zone, of which 12 schools have been selected as samples. Totally 92 student samples were selected by using Krejcie Morgan sampling method along with 12 principals, 12 vice-principals, and 24 teachers. A simple transliteration method was used, and data were collected using questionnaires from the students, and interviews with teachers and principals, and data from documents. The collected data were analyzed descriptively using tables and graphs. The prevalence of the students who selected the Health and Physical education as the subject among these school is 24 (mean value). The benefits of studying this subject encountered by the participants are: students may acquire skills in goal planning, time management, self-monitoring, reasoning, problem-solving, flexibility, accountability, attention control, and self-confidence. Also, it was suggested that students’ achievement and logical thinking abilities can be enhanced through this subject. Many participants stated that if the students studying this subject, it may be benefited for their wellbeing. Since the percentage of choosing this subject is less, it was recommended that students and parents in the study area to be educate regarding the benefits of this subject.
Keywords: Health and physical education; Sri Lankan curriculum; Benefits; Health subject; Health science; School